RISK FACTORS FOR CHRONIC NONCOMMUNICABLE DISEASES IN THE MINISTRY OF EMERGENCY SITUATIONS PERSONNEL - E.YU. SHKATOVA; I.A. KOBILYATSKAYA (Avicenna Tajik State Medical University, 2021)
Objective: To establish risk factors (RFs) for the development of noncommunicable diseases (NCDs) among the Ministry of Emergency Situations (MChS) personnel. Methods: To identify the RFs for the development of NCDs, the health status of 205 MChS staff members of the Udmurt Republic, Russia, was assessed by a social survey according to a specially developed form «Social and hygienic profile of the MChS employee». In addition, the method of regression analysis, multiple linear regression, was selected to identify risk factors for NCDs. Results: Regression analysis showed that the MChS personnel health status is influenced in decreasing order by socio-hygienic, medico-biological, and professional factors. At the same time, the development of NCDs was significantly influenced by the complex of all identified RFs (R2=0.69; F=4.93; p=0.0001). The following statistically significant RFs for the development of chronic diseases in the MChS personnel were identified: work exposure of 6 years or more; frequent round the clock shifts; smoking; negative family emotional climate; a high level of state and trait anxiety, age 33 and above, and passive recreational use. Failure to maintain a healthy lifestyle (HL) is referred to as «borderline» RF. Conclusion: The identified RFs will promote development of the programs of NCDs prevention among the MChS personnel. Particular attention should be paid to educational technologies promoting health-related activities and good hygiene practices when developing programs.